Risk factors for residual acetabular dysplasia after closed reduction treatment of developmental dysplasia of the hip: a systematic review and meta-analysis - Chen, Min; Qian, Jun; Weng, Li; Zhang, Ai-Xia; Cai, Ru-Yi (Frontiers in Pediatrics, 2026)
BackgroundResidual acetabular dysplasia (RAD) is a common complication following closed reduction (CR) for developmental dysplasia of the hip (DDH). This study aims to perform a meta-analysis to identify predictive factors for RAD in order to provide a theoretical basis for early clinical identification and prevention.MethodsA comprehensive literature search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library databases, covering the period from database inception to November 2024. The quality of the included studies was assessed using the Newcastle–Ottawa Scale, and data analysis was performed using StataSE-64 and RevMan 5.4 software. The odds ratio (OR) and 95% confidence interval (CI) were used for data synthesis. Evidence for all outcomes was graded according to the GRADE system.ResultsThis meta-analysis included 16 studies, including a total of 1,338 children who underwent CR for DDH. The analysis identified female sex (OR: 1.96; 95% CI: 1.01–3.81; p = 0.05) and femoral head coverage (FHC) (OR: 0.95; 95% CI: 0.92–0.97; p = 0.0002) as risk factors for RAD after CR. However, acetabular index (AI) (OR: 1.11; 95% CI: 0.94–1.31; p = 0.21), treatment age (<1 year vs. ≥1 year) (OR: 1.16; 95% CI: 0.95–1.42; p = 0.13), side of DDH occurrence (OR: 0.84; 95% CI: 0.52–1.36; p = 0.48), and number of affected sides (OR: 0.76; 95% CI: 0.05–12.72; p = 0.85) were not identified as risk factors for RAD. According to the GRADE assessment, all indicators were rated as “very low-quality evidence,” except for FHC, which was classified as “low-quality evidence.”ConclusionThe results of this study indicate that female sex and FHC are the primary risk factors for RAD after CR treatment of DDH. Given the inherent limitations of this study, further multicenter prospective clinical studies are needed to clarify the factors contributing to RAD after CR in children with DDH and to implement preventive measures to improve the long-term prognosis of these children.Systematic Review RegistrationPROSPERO CRD420251016618.